Trans-cellular introduction of HIV-1 protein Nef induces pathogenic response in Caenorhabditis elegans. - Aamir Nazir (Public Library of Science (PLoS), 2010)
Background Caenorhabditis elegans has emerged as a very powerful model for studying the host pathogen interactions. Despite the absence of a naturally occurring viral infection for C. elegans, the model is now being exploited experimentally to study the basic aspects of virus-host interplay. The data generated from recent studies suggests that the virus that infects mammalian cells does infect, replicate and accumulate in C. elegans. Methodology/principal findings We took advantage of the easy-to-achieve protein introduction in C. elegans and employing the methodology, we administered HIV-1 protein Nef into live worms. Nef is known to be an important protein for exacerbating HIV-1 pathogenesis in host by enhancing viral replication. The deletion of nef from the viral genome has been reported to inhibit its replication in the host, thereby leading to delayed pathogenesis. Our studies, employing Nef introduction into C. elegans, led to creation of an in-vivo model that allowed us to study, whether or not, the protein induces effect in the whole organism. We observed a marked lipodystrophy, effect on neuromuscular function, impaired fertility and reduced longevity in the worms exposed to Nef. The observed effects resemble to those observed in Nef transgenic mice and most interestingly the effects also relate to some of the pathogenic aspects exhibited by human AIDS patients. Conclusions/significance Our studies underline the importance of this in vivo model for studying the interactions of Nef with host proteins, which could further be used for identifying possible inhibitors of such interactions.